Hooked on heart regeneration: the zebrafish guide to recovery. Issue 7 (23rd June 2021) - Ross Stewart, Katherine M; Walker, Sophie L; Baker, Andrew H; Riley, Paul R; Brittan, Mairi
Abstract: While humans lack sufficient capacity to undergo cardiac regeneration following injury, zebrafish can fully recover from a range of cardiac insults. Over the past two decades, our understanding of the complexities of both the independent and co-ordinated injury responses by multiple cardiac tissues during zebrafish heart regeneration has increased exponentially. Although cardiomyocyte regeneration forms the cornerstone of the reparative process in the injured zebrafish heart, recent studies have shown that this is dependent on prior neovascularization and lymphangiogenesis, which in turn require epicardial, endocardial, and inflammatory cell signalling within an extracellular milieu that is optimized for regeneration. Indeed, it is the amalgamation of multiple regenerative systems and gene regulatory patterns that drives the much-heralded success of the adult zebrafish response to cardiac injury. Increasing evidence supports the emerging paradigm that developmental transcriptional programmes are re-activated during adult tissue regeneration, including in the heart, and the zebrafish represents an optimal model organism to explore this concept. In this review, we summarize recent advances from the zebrafish cardiovascular research community with novel insight into the mechanisms associated with endogenous cardiovascular repair and regeneration, which may be of benefit to inform future strategies for patients with cardiovascular disease. Graphical Abstract: